George Zubrzycki giving an ANU Convocation luncheon address entitled The Boat People on 3 May 1979 - Zubrzycki, Jerzy, 1920-2009.; Australian National University (1979)
Professor Zubrzycki talks about a personal encounter he had with some Vietnamese refugees he met when they arrived in Darwin. He recounts the racial prejudice he encountered in a group of students he lectured. He explains why there are refugees and Australia's responsibility to them. He examines the moral issues of refugees and puts forward his theory on refugee assimilation. He then answers questions questions from the audience.
Recorded on 3 May 1979 at the Australian National University, Canberra, Australian Capital Territory.
Digital master available
Keywords: Australian National University. -- Department of Sociology -- Professional staff; College teachers -- Australian Capital Territory; Sociologists -- Australian Capital Territory; Refugees -- Vietnam; Refugees -- Government policy -- Australia; Vietnamese -- Cultural assimilation -- Australia; Lectures and lecturing -- Australian Capital Territory; Academics; Sociologists